[PP.03.23] URIC ACID LEVELS PREDICT CORONARY ARTERY DISEASE BUT NOT STROKE IN ESSENTIAL HYPERTENSION: DATA FROM A GREEK 8-YEAR-FOLLOW-UP STUDY. (September 2016) - Dimitriadis, K.; Tsioufis, C.; Konstantinidis, D.; Kalos, Th; Vlachos, G.; Lagiou, F.; Galanakos, S.; Tousoulis, D.
Abstract : Objective: The exact role of uric acid in cardiovascular risk prediction remains to be further determined. The aim of the present study was to assess the predictive role of uric acid for the incidence of coronary artery disease (CAD) as well as stroke in essential hypertensive patients. Design and method: We followed up 2415 essential hypertensives (mean age 58.4 years, 1208 males, office blood pressure (BP)=143/88 mmHg) for a mean period of 8 years. All subjects had at least one annual visit and at baseline underwent echocardiographic study and blood sampling. Moreover, CAD was defined as the history of myocardial infarction or significant coronary artery stenosis and stroke was defined as rapid onset of a new neurological deficit persisting at least 24 hours unless death supervened confirmed by imaging findings. Results: The incidence of CAD and stroke was 2.2% and 1% respectively. Hypertensives who developed CAD (n = 53) compared to those without CAD at follow-up (n = 2362) had at baseline higher baseline uric acid levels (5.8 ± 1.8 vs 5.2 ± 1.5 mg/dl, p = 0.011), left ventricular mass index (LVMI) (115.7 ± 27.1 vs 103.7 ± 27.1 g/m 2, p = 0.001) and prevalence of LV hypertrophy (41% vs 25%, p = 0.017) whereas no difference was observed with respect to baseline office BP, renal function and lipid levels (p = NS for all). Hypertensives who developed stroke (n = 24) compared to those without CAD at follow-up (n = 2391) were older (63 ± 8 vs 58 ± 11 years, p = 0.006) whereas no difference was observed with respect to baseline office BP, uric acid, renal function and lipid levels (p = NS for all). Univariate Cox regression analysis revealed that baseline uric acid levels predicted CAD (hazard ratio = 1.219, p = 0.013) but not stroke. In multivariate Cox regression model baseline glomerular filtration rate (hazard ratio = 1.018, p = 0.017) LVMI (hazard ratio = 1.010, p = 0.026) and uric acid (hazard ratio = 1.226, p = 0.016) turned out to be independent predictors of CAD, while age (hazard ratio = 1.058, p = 0.014) predicted stroke. Conclusions: In essential hypertensive patients uric acid predicts future development of CAD, whereas exhibits no prognostic value for stroke. These findings further support that uric acid estimation could improve overall risk stratification in essential hypertension.